A Brief Review of the Industrial Manipulators in Product-line - Abdolreza, Toudehdehghan; Ebadullah, Wardak (INTI International University, 2022)
This article provides a comprehensive overview of the industrial manipulator, brief history, classification, application, and design process. It is crucial for designers, engineers, and researchers to be familiar with various types of industrial manipulators and applied codes used by engineering companies, as well as key factors that need to be considered during the design process. This paper provides a basic understanding of the industrial manipulators in order to optimize the current manipulator design and propose new designs. To optimize and construct the design, it is necessary to understand different types of errors related to the design and the codes that lead us to a suitable design. These error types and codes have been explained in detail in this document.